The Effect of Empathy on Patient Satisfaction in Hemodialysis Services: A SERVQUAL-Based Cross-Sectional Study - Dinnisa Haura Zhafira; Yona Mimanda; Mahesa Paranadipa Maikel; Tri Nisa Widyastuti (The Avicenna Medical Journal, 2024)
Background: Empathy is a fundamental aspect of healthcare service quality and plays a vital role in influencing patient satisfaction, especially in long-term, high-contact treatments such as hemodialysis. Despite its importance, limited research in Indonesia has specifically explored the impact of empathy on patient satisfaction in hemodialysis settings. This study aims to evaluate the effect of empathy on patient satisfaction among individuals receiving hemodialysis at Jakarta Hajj Hospital using the SERVQUAL framework. Methods: A quantitative, cross-sectional study was conducted at Jakarta Hajj Hospital between November and December 2022, involving 118 hemodialysis patients selected through consecutive sampling. Data were collected using a structured questionnaire adapted from the KKP-2017 and SERVQUAL instruments. Statistical analysis included descriptive statistics, followed by assumption tests (normality, linearity, and heteroscedasticity), and simple linear regression using SPSS version 26. Results: The mean empathy score was 3.47 ± 0.63. Simple linear regression indicated that empathy had a statistically significant effect on patient satisfaction (B = 0.701, SE = 0.084, 95% CI [0.535–0.868], β = 0.613, R² = 0.375, p < 0.001). The fitted model was: Patient Satisfaction = 13.24 + 0.701(Empathy). Conclusion: Empathy significantly contributes to patient satisfaction in hemodialysis services. Strengthening empathetic communication and patient-provider relationships may enhance service quality and overall patient experiences in chronic care environments.